RANCANG BANGUN MESIN PENCACAH SAMPAH ORGANIK - saparin; Muhammad Nurdiansyah; Yudi Setiawan; Eka Sari Wijianti (Politeknik Negeri Sriwijaya, Indonesia, 2023)
This research is about designing an organic waste-shredder machine. The aims are to calculate the production capacity and efficiency of the machine. Machine dimensions are: length, width, and height are 1035 mm, 320 mm, and 955 mm respectively. There are three types of blades; chopping blades, fixed blades, and pulling blades. There are four blades for the chopper, with dimensions of 240 mm in length, 50 mm in width, and 50 mm in thickness. The distance of the shredder blade to the fixed blade is 2 mm. The angle of the shredder blade is 20 degrees. The internal combustion engine with a power of 7 PK is used to drive the shaft. The criterion for successful enumeration was the maximum size of 4 cm. The machine capable of chopping using twigs of ketapang is 103.29 kg/hour and the coconut midrib is 282.96 kg/hour. Machine production efficiency using twigs of ketapang is 88.83% and coconut midrib is 76.4%.